Program Keluarga Berencana Ditinjau dari Perspektif Alkitab - Welikinsi, Welikinsi (Jurnal Kala Nea, 2022)
The purpose of this study is to explain the government's goals for implementing family planning programs and to describe the biblical view of family planning programs. The background of this research is the way of life of the people who do not really care about family planning programs so that population growth has a negative impact and results in high and growing unemployment rates, this causes limited job opportunities. This research uses descriptive qualitative research with an approach to the family planning program which is one of the government's efforts to control the rate of population growth in overcoming the negative impacts that occur. Data collection techniques were carried out by observing the objectives of the family planning program and how the Bible views family planning programs. The biblical perspective provides an understanding that the existence of a family planning program is an effort by the government to control the rate of population growth and form quality families.